Research on the Path of Integrating Excellent Traditional Chinese Culture into College English Teaching - Zhang, Yahui (Pacific International Journal, 2024)
This paper aims to explore the path of integrating excellent traditional Chinese culture into college English teaching, so as to improve the cross-cultural communication ability and cultural literacy of English majors and enhance cultural confidence. Through comprehensive analysis of relevant literature, questionnaires, interviews and teaching practice, this study finds that integrating excellent traditional Chinese culture into college English teaching is of great significance and can be achieved through multiple paths such as curriculum setting, textbook compilation, teaching methods, improvement of teachers' qualities and extracurricular activities. At the same time, this paper also puts forward some suggestions and countermeasures to promote the better integration of excellent traditional Chinese culture into college English teaching.